BNBM : synergic innovation targeting the commanding heights - Li, Jizhen, (SAGE Business Cases., 2017)
The case focuses on BNBM, the only national-level innovative enterprise in the new building materials industry in China, which has been focusing on independent innovation and technological breakthroughs in the gypsum board sector for many years. The case describes how BNBM, a state owned enterprise, promoted innovation and development and completed a technological development plan.